Altered Gut Microbiota in Patients With Peutz–Jeghers Syndrome - Wang, Sui; Huang, Gang; Wang, Jue-Xin; Tian, Lin; Zuo, Xiu-Li; Li, Yan-Qing; Yu, Yan-Bo (Frontiers in Microbiology, 2022)
Background: Peutz–Jeghers syndrome (PJS) is a rare genetic disorder characterized by the development of pigmented spots and gastrointestinal polyps and increased susceptibility to cancers. It remains unknown whether gut microbiota dysbiosis is linked to PJS. Aim: This study aimed to assess the structure and composition of the gut microbiota, including both bacteria and fungi, in PJS patients and investigate the relationship between gut microbiota dysbiosis and PJS pathogenesis. Methods: The bacterial and fungal composition of the fecal microbiota was analyzed in 23 patients suffering from PJS (cases), 17 first-degree asymptomatic relatives (ARs), and 24 healthy controls (HCs) using 16S (MiSeq) and ITS2 (pyrosequencing) sequencing for bacteria and fungi, respectively. Differential analyses of the intestinal flora were performed from the phylum to species level. Results: Alpha diversity distributions of bacteria and fungi indicated that the abundance of both taxa differed between PJS cases and controls. However, while the diversity and composition of fecal bacteria in PJS cases were significantly different from those in ARs and HCs, fungal flora was more stable. High-throughput sequencing confirmed the special characteristics and biodiversity of the fecal bacterial and fungal microflora in patients with PJS. They had lower bacterial biodiversity than controls, with a higher frequency of the Proteobacteria phylum, Enterobacteriaceae family, and Escherichia-Shigella genus and a lower frequency of the Firmicutes phylum and the Lachnospiraceae and Ruminococcaceae families. Of fungi, Candida was significantly higher in PJS cases than in controls. Conclusion: The findings reported here confirms gut microbiota dysbiosis in patients with PJS. This is the first report on the bacterial and fungal microbiota profile of subjects with PJS, which may be meaningful to provide a structural basis for further research on intestinal microecology in PJS.